Increased bleeding events with the addition of apixaban to the dual anti-platelet regimen for the treatment of patients with acute coronary syndrome: A meta-analysis. Issue 12 (26th March 2021) - Jin, Jing; Zhuo, Xiaojun; Xiao, Mou; Jiang, Zhiming; Chen, Linlin; Devi Shamloll, Yashvina
Abstract: Background: Dual anti-platelet therapy (DAPT) with aspirin and clopidogrel has been the mainstay of treatment for patients with acute coronary syndrome (ACS). However, the recurrence of thrombotic events, potential aspirin and clopidogrel hypo-responsiveness, and other limitations of DAPT have led to the development of newer oral anti-thrombotic drugs. Apixaban, a new non-vitamin K antagonist, has been approved for use. In this meta-analysis, we aimed to compare the bleeding outcomes observed with the addition of apixaban to DAPT for the treatment of patients with ACS. Methods: Online databases including EMBASE, Cochrane Central, http://www.ClinicalTrials.gov, MEDLINE and Web of Science were searched for English based publications comparing the use of apixaban added to DAPT for the treatment of patients with ACS. Different categories of bleeding events and cardiovascular outcomes were assessed. The analysis was carried out by the RevMan software version 5.4. Odds ratios (OR) with 95% confidence intervals (CI) were used to represent the data following analysis. Results: This research analysis consisted of 4 trials with a total number of 9010 participants. Thrombolysis in myocardial infarction (TIMI) defined major bleeding (OR: 2.45, 95% CI: 1.45–4.12; P = .0008), TIMI defined minor bleeding (OR: 3.12, 95% CI: 1.71–5.70; P = .0002), International society of thrombosis and hemostasis (ISTH) major bleeding (OR: 2.49, 95% CI: 1.80–3.45; P = .00001) and Global Use of Strategies to Open Occluded Arteries (GUSTO) defined severe bleeding (OR: 3.00, 95% CI: 1.56–5.78; P = .01) were significantly increased with the addition of apixaban to DAPT versus DAPT alone in these patients with ACS. However fatal bleeding (OR: 10.96, 95% CI: 0.61–198.3; P = .11) was not significantly different. Conclusions: Addition of the novel oral anticoagulant apixaban to the DAPT regimen significantly increased bleeding and therefore did not show any beneficial effect in these patients with ACS. However, due to the extremely limited data, we apparently have to rely on future larger studies to confirm this hypothesis.